Gagasan Pemikiran Rahmah El-Yunusiyah tentang Pendidikan Islam bagi Perempuan - Arwan Dermawan; Eka Putra Wirman; Sarwan Sarwan (Jurnal Budi Pekerti Agama Islam, 2024)
Rahmah's belief in the role of education as one of the right ways to raise the status of women has been held since she was a teenager. Therefore, Rahmah wanted to establish a special religious college for women. This research aims to find out how Rahmah El-Yunusiyah's ideas on Islamic education for women. The method used in this research is the Systematic literature review (SLR) method. The data of this research is taken from the google scholar database, the author uses google scholar as the main source of information by analyzing documents related to Rahmah El-Yunusiyah's ideas on Islamic Education for women. The results showed that a woman must learn as high as possible because a woman is the first madrasa for future generations, so this is what Rahmah El-Yunusiyah has always fought for in raising the status of women to get learning, but in fighting for this it cannot be separated from the pros and cons but it all does not eliminate Rahmah El-Yunusiyah's enthusiasm in fighting for gender equality in education by establishing AL-Madrasah AL-Diniyyah Li Al-Banat.